Design and synthesis of a s-triazene based asymmetric organocatalyst and its application in enantioselective alkylation1. Issue 75 (19th August 2015) - Mangawa, Shrawan K.; Singh, Ashawani K.; Awasthi, Satish K.
<x xml:space="preserve">Abstract</x> A very efficient chiral organocatalyst was prepared from the readily available cyanuric chloride.